(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Tomashevskiy V. V. The problem of the professional preparation of future designers in the system of the higher education. In article is considered the role of the aesthetic culture in process of the professional preparation of future designers the system of the higher education on the contemporary stage of society’s development, and also her structure, represented the character of separate structure components, in particular aesthetic consciousness and aesthetic activity, their categories.